Impact of Neck PET/CT Positivity on Survival Outcomes—Visual and Quantitative Assessment: Results From ACRIN 6685. (7th February 2023) - Stack, Brendan C.; Duan, Fenghai; Romanoff, Justin; Sicks, JoRean D.; Subramaniam, Rathan M.; Lowe, Val J.
Abstract : Introduction: FDG PET/CT was prospectively studied in 287 cN0 head and neck cancer patients in ACRIN 6685, and additional analysis of neck FDG uptake upon recurrence-free survival (RFS) and overall survival (OS) was performed. Patients and Methods: Two hundred eight had analyzable data. Survival analysis was performed to compare RFS and OS based on neck FDG visual assessment (VA) and SUVmax . For SUVmax, the optimal thresholds were calculated using conditional inference trees on a randomly selected 70% training data set and validated using the remaining 30% of data. Kaplan-Meier curves with log-rank tests were generated for the patient groups based on VA and optimal SUVmax thresholds, and the hazards ratios (HRs) and 95% confidence intervals (CIs) were also calculated. Hypothesis testing was set at a significance level of 0.05. Results: A total of 73.9% of bilateral cN0 and 50.0% of unilateral cN0 were alive at the end of the study with the remaining being dead or lost to follow-up. Overall survival median follow-up time was 24.0 months (interquartile range, 15.8–25.3; range, 0–37.0). A total of 63.3% of bilateral cN0 and 42.5% of unilateral cN0 patients remained disease free during the study. Recurrence-free survival median follow-up time was 23.9 months (interquartile range, 12.4–25.2; range, 0–35.6). Visual assessment of necks by our panel of radiologists was significantly associated with RFS (HR [95% CI], 2.30 [1.10–4.79]; P = 0.02), but not with OS (HR [95% CI], 1.64 [0.86–3.14]; P = 0.13). The optimal SUVmax thresholds were 2.5 for RFS and 5.0 for OS. For SUVmax assessment, applying the optimal thresholds to the 30% test data yielded HRs (95% CIs) of 2.09 (0.61–7.14; P = 0.23) for RFS and 3.42 (1.03–11.41; P = 0.03) for OS. The SUVmax threshold of 5.0 was significantly associated with RFS (HR [95% CI], 5.92 [1.79–19.57]; P < 0.001). Conclusions: Neck FDG uptake by VA is significant for RFS. An SUVmax threshold of 5.0 is significantly associated with OS and RFS.